Software for modeling, simulation and programming robotic applications - Velásquez Costa, José Antonio (2009)
Currently there is a wide range of software to simulate robotic cell and interact with a process. This article details the procedure to simulate and program a robotic system of classification of items using the software Cosimir Educational. The project includes a window model, positions and programming. Programming is performed using the language Mitsubishi Robot Language (MRL), which is simple but with enough capacity to perform tasks with the robot. This language has commands for movement control, counters, timers, subroutines, loops and incorporates input and output signals.